2021
DOI: 10.11646/zootaxa.5068.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Two new species of Rhinogobius (Gobiiformes: Oxudercidae) from Palawan, Philippines, with their phylogenetic placement

Abstract: Two new species of Rhinogobius found in streams on central part of Palawan Island, Philippines are described. The two new species, Rhinogobius estrellae and Rhinogobius tandikan share unique transverse rows of sensory papillae on the cheek with Rhinogobius similis Gill, 1859, but differ from the latter in fin ray counts, arrangement of the scales, etc. The two new species are distinguished from each other by the pectoral-fin ray count, the longitudinal- and predorsal-scale counts, and colouration of the body. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 484 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“… 2020 ; Maeda et al. 2021 ). As shown in Figure 3 , the topological structure of the phylogenetic tree showed that R. szechuanensis and R. rubromaculatus gathered together, and they formed a sister group with the group include R. leavelli , Rhinogobius davidi, and Rhinogobius similis.…”
Section: Resultsmentioning
confidence: 99%
“… 2020 ; Maeda et al. 2021 ). As shown in Figure 3 , the topological structure of the phylogenetic tree showed that R. szechuanensis and R. rubromaculatus gathered together, and they formed a sister group with the group include R. leavelli , Rhinogobius davidi, and Rhinogobius similis.…”
Section: Resultsmentioning
confidence: 99%
“… 2015 ), R. estrellae (Maeda et al. 2021 ), and R. tandikan (Maeda et al. 2021 ), while R. filamentosus , R. duospilus (Tan et al.…”
Section: Resultsmentioning
confidence: 99%
“… 2021 ), and R. tandikan (Maeda et al. 2021 ), while R. filamentosus , R. duospilus (Tan et al. 2020 ), and other ten species ( R. nagoyae (Maeda et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations